CIPP Evaluation Model and Its Effect on E-Learning - Darul Prayogo (AL-ISHLAH: Jurnal Pendidikan, 2022)
One indicator of the quality of educational institutions is the use of information technology in teaching and learning activities. E-learning is fundamentally a teaching and learning activity using internet-based technology. This research aims to evaluate teaching and learning activities using e-learning. This study utilized the CIPP (Context, Input, Process, Product) evaluation model related to e-learning. The analysis technique used was multiple linear regression using R Software to see how much effect context and Input had on the learning process and how much Context and Input had on the learning product. Based on the study results, knowledge and understanding of the Context component were of more significant concern since 63 (44.68%) of 141 cadets stated ‘poor’. The average score of knowledge and understanding of the Input component was 41, which was in score interval 33 – 42, included in the good category. Moreover, the average score of knowledge and understanding of the Process component was 82, which was in score interval 65 - 84, included in the good category. Importantly, knowledge and understanding of the Product component were of greater concern since 69 (48.94%) of 141 cadets showed poor results. The effect size of Context and Input components on the process was 0.5479 or 54.79%, while the remaining 45.21% was affected by other factors not examined in this study. The input component had a significantly greater effect on the Process component with a significance level of 0.001 than the Context component. Moreover, the effect size of Context and Input components on the Product was 0.3303 or 33.03%, while the remaining 66.97% was affected by other factors not examined in this study. The context component had a significantly greater effect on the Product with a significance level of 0.001 than the Input component.